2022
DOI: 10.1155/2022/1456382
|View full text |Cite|
|
Sign up to set email alerts
|

Using Social Media Data to Explore Urban Land Value and Sentiment Inequality: A Case Study of Xiamen, China

Abstract: Differences in urban land values affect residents' living experiences and may contribute to sentiment inequality. Due to the popularity of smart mobile devices and social media platforms, online tweets with location information can be used as objective information to reflect sentiment differences of urban residents in different locations, overcoming the limitations of previous studies with small sample sizes or a lack of spatial information. Sentiment quantification based on deep learning enables the identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…To get a better understand of the spatial characteristics of the distribution of the sentiment index and its spatial relationship with the urban environment, this study employed a 200 m × 200 m grid as a basic statistic unit, the sentiment index and the urban environment indicators in each cell were aggregated based on the averages. In addition, the grid with a small number of samples was deleted, and the average sentiment index of each grid was obtained based on the following formula to ensure the normal distribution of data and eliminate the influence of outliers ( Gai et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…To get a better understand of the spatial characteristics of the distribution of the sentiment index and its spatial relationship with the urban environment, this study employed a 200 m × 200 m grid as a basic statistic unit, the sentiment index and the urban environment indicators in each cell were aggregated based on the averages. In addition, the grid with a small number of samples was deleted, and the average sentiment index of each grid was obtained based on the following formula to ensure the normal distribution of data and eliminate the influence of outliers ( Gai et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…It was also found that floating population settlement spaces have a negative effect on the daytime touring experience of residents in UGSs, which may be because these spaces are commonly found on the outskirts of suburban and central urban areas. Moreover, floating populations often choose to live in low-cost locations where UGSs have low construction funds and poor quality, making it difficult for them to meet the recreational needs of residents [97]. The proportion of the floating population was found to be the only external urban form factor explanatory variable affecting the daytime touring experience, with each one standard deviation increase decreasing the daytime touring experience by 0.30 standard deviations.…”
Section: Touring Experiencementioning
confidence: 98%
“…Then, 10,000 points of SMTD were manually labeled with sentiments. Machine learning based on pre-trained samples teaches computers how to quantify sentiments in SMTD [97]. Unlike scoring methods, such as sentiment dictionaries and cloud sentiment analysis [89], the localized SKEP method is similar to human subjective thinking, and the method is reproducible.…”
Section: Identifying the Sentiments Of Resident Activities In Ugss Us...mentioning
confidence: 99%
See 1 more Smart Citation
“…There are also some specific applications of SKEP used in this paper. Gai et al [18] used the SKEP pre-trained model provided by Baidu intelligent cloud sentiment analysis platform to identify 460,000 Weibo tweets from Xiamen, China in 2020 for studying inequalities between urban residents' sentiments and land values.…”
Section: Chinese Sentiment Analysismentioning
confidence: 99%